Embodied Knowing: Getting Back to our Roots - Randee Lipson Lawrence; Yolanda Nieves; Celeste Snowber; Luis Kong; Gabo Ntseane (Adult Education Research Conference, 2013)
Embodied knowing is explored as an intuitive process, through women’s stories, through dance, as community building through martial arts and through interactions with animals at an African game drive. Implications for adult education are discussed.